The development of the theory of unlawful acts in civil law regarding gender inequality and social justice values - Murti; Setianingsih, Elin; Fristia Maulana, Ayang (Institute Of computer Science (IOCS), 2025)
This study examines the development of the theory of unlawful acts (UNL) in Indonesian civil law and its contribution to addressing gender inequality and achieving social justice values. The main focus lies on how civil law, which was initially neutral and individualistic, has undergone a transformation in responding to structural issues such as gender-based discrimination. This study was conducted by tracing various classical to contemporary legal literature, both from national and international perspectives, in order to understand how the concept of UNL has developed in theoretical and applied dimensions. The results of the review show that the UNL theory, which was initially limited to violations of formal legal norms, has experienced an expansion of meaning to include violations of norms of propriety, morality, and basic rights that are socially protected. In the context of gender inequality, it was found that civil law often produces inequality through formally neutral interpretations but ignores the unequal social structural context. Feminist literature and social justice theory then propose a reinterpretation of UNL to be more responsive to violations that are systemic and discriminatory against women. This study concludes that the reconstruction of UNL needs to be directed towards the paradigm of substantive and inclusive justice.